The Effect Of Pop Up Book Media On Student Learning Outcomes In The Subject Of Sciences In Grade IV - Rodearnita Sinaga; Lisbet Sihombing; Janwar Tambunan (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the effect of Pop-Up Book media on student learning outcomes in the IPAS subject for Grade IV at UPTD SD Negeri 122371 Pematangsiantar. The research used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 25 Grade IV students. The instrument used was a multiple-choice test. Based on statistical data analysis using the normality test, the value obtained was 0.192, which is greater than 0.05, indicating that the data is normally distributed. The results of the t-test showed that the calculated t-value was 9.891, while the table t-value was 2.064, meaning t_count > t_table (9.891 > 2.064). This indicates a significant difference between pretest and posttest scores, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). Therefore, it can be concluded that Pop-Up Book media has a significant effect on student learning outcomes in the IPAS subject for Grade IV at UPTD SD Negeri 122371 Pematangsiantar.